Implikasi UU ITE terhadap Kebebasan Pers menurut Perspektif Teori Lawrence M. Friedman - Fina Khoirunnisa; M. Haikal Nazar Shohib; Fariha Qonita Salma (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
As a democratic legal state, Indonesia is obligated to guarantee press freedom as an information source for the community and as a social watchdog. The ITE Law, a response to technological developments, affects the existence of press media, which now present information digitally. This research focuses on two main issues: First, it examines the implications of the ITE Law on press freedom using Lawrence M. Friedman's theory. Second, it explores how to ideally guarantee press freedom through the legal protection of journalists. This study aims to examine the extent to which the ITE Law restricts press freedom. This study employs a normative juridical approach with a literature review and case analysis of the criminalization of journalists in Indonesia. The results show that the ITE Law creates legal ambiguity, thus triggering the abuse of vague articles, particularly Article 26, paragraph 3, which contradicts press freedom as protected by the 1945 Constitution. The study concludes that there is a need for a fundamental revision of the ITE Law to create a balance between individual rights and public interests. Alternative solutions include synchronizing the law with the press law and strengthening the role of the Press Council.